Meningkatkan Daya Saing UMKM Perempuan Surabaya: Workshop Praktis tentang Strategi Pemasaran - Novie Noordiana Rachma Yulia; Agus Purbo Widodo; Wahyu Rochana; Arlisa Indriawati; Agung Pribadhi; Ady Setiawan; Heri Sudarsono; Puput Artalia (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
This community service activity aimed to enhance the competitiveness of women-led Micro, Small, and Medium Enterprises (UMKM) in Surabaya by providing practical marketing strategies through a workshop. Despite their significant role in the national economy, many UMKM, especially those run by women, face challenges in marketing due to limited access to training and resources. This workshop, held at Darmo Trade Center, Surabaya, focused on providing simple yet applicable marketing strategies, such as the STP (Segmentation, Targeting, Positioning) framework and the Unique Selling Proposition (USP) to help entrepreneurs better understand their products, target consumers, and improve product differentiation. The workshop also emphasized entrepreneurial characteristics and business risk-taking. The results indicated that the participants, mostly women entrepreneurs, gained valuable insights into marketing strategies and felt more confident in applying these concepts to improve their business performance. Feedback from the participants suggested a high level of engagement and readiness to implement the strategies discussed.